قياس وتحليل اثر المساعدات المالية الدولية في النمو الاقتصادي للدول منخفضة الدخل للمدة 1990 - 2019 - الجبوري، مخيف جاسم حمد; جاسم، محمد سلمان; عبدالله، جمال حسين علي (الجامعة المستنصرية - كلية الإدارة والاقتصاد, 2021)
The international aid in the last decade is a source of funding for most developing countries and at their various levels, especially for low-income countries. The aim of the research is to identify the trends of financial aid and the per capita share of it on the economic growth of the group of low-income countries. The research found the stability of the variables data at the first difference. And a very high moral level, which led to the possibility of conducting co-integration of degrees (0,1) and (1,1), which proved the existence of a long-term relationship between the research variables, The standard results of the estimated model also proved that there is a positive relationship between financial aid and economic growth in the case of directing this aid to building social capital. However, the standard results proved that the increase in the per capita share of such aid leads to a decrease in GDP, as it was insignificant and associated with Aid has a positive relationship stronger than its correlation with GDP, and the independent variables explained about (72%) of the changes of the dependent variable, and there was no self-correlation, and the model was significant, as the value of F () reached a significant degree, and the research recommends activating the role of financial aid and directing it towards Building social capital and supporting poor families and budget deficits for low-income countries.
تعد المساعدات الدولية في العقد الأخير مصدر من مصادر التمويل لأغلب الدول النامية وبمختلف مستوياتها وخاصة للدول ذات الدخل المنخفض، هدف البحث إلى التعرف على اتجاهات المساعدات المالية ونصيب الفرد منها على النمو الاقتصادي لمجموعة الدول منخفضة الدخل، وقد توصل البحث إلى استقرار بيانات المتغيرات عند الفرق الأول وبدجة معنوية عالية جدا مما أدى ذلك إلى إمكانية إجراء التكامل المشترك من الدرجة (0.1) و (1.1) والذي أثبت وجود علاقة طويلة الأمد بين متغيرات البحث، كذلك أثبتت النتائج القياسية للنموذج المقدر وجود علاقة إيجابية بين المساعدات المالية والنمو الاقتصادي في حالة توجيه هذه المساعدات إلى بناء رأس المال الاجتماعي لكن أثبتت النتائج القياسية أن ارتفاع نصيب الفرد في تلك الدول من هذه المساعدات يؤدي إلى انخفاض الناتج المحلي الإجمالي حيث كانت غير معنوية وترتبط مع المساعدات بعلاقة موجبة أقوى من ارتباطها مع الناتج المحلي الإجمالي كما أن المتغيرات المستقلة فسرت حوالي (72%) من تغيرات المتغير التابع، وعدم وجود ارتباط ذاتي، والنموذج معنوية حيث بلغت قيمة F (38.467) درجة معنوية عالية، ويوصي البحث بتفعيل دور المساعدات المالية وتوجيهها نحو بناء رأس المال الاجتماعي ودعم الأسر الفقيرة وعجز الموازنة للدول منخفضة الدخل.
Keywords: المساعدات المالية -- النمو الاقتصادي -- الدول النامية -- القطاعات الاقتصادية